2016
DOI: 10.1080/10810730.2016.1250846
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of eHealth Literacy on Perceived Trust in Online Health Communication Channels and Sources

Abstract: Disparities in online health information accessibility are partially due to varying levels of eHealth literacy and perceived trust. This study examined the relationship between eHealth literacy and perceived trust in online health communication channels and sources among diverse socio-demographic groups. A stratified sample of Black/African Americans (n = 402) and Caucasians (n = 409) completed a web-based survey that measured eHealth literacy and perceived trustworthiness of online health communication channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 51 publications
2
91
0
1
Order By: Relevance
“…Examination of different internet sources was beyond the scope of this study (the term “internet” was used in a general sense); future research needs to examine the way in which information is presented online and the extent to which the information is perceived as credible by parents. We know that consumers deem web‐based information as more credible when it is easy to access and understand (Ye, ), and tailored to specific demographics, such as age and race, as sociodemographic differences can play a role in the sources used and the degree of credibleness assigned (Paige, Krieger, & Stellefson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of different internet sources was beyond the scope of this study (the term “internet” was used in a general sense); future research needs to examine the way in which information is presented online and the extent to which the information is perceived as credible by parents. We know that consumers deem web‐based information as more credible when it is easy to access and understand (Ye, ), and tailored to specific demographics, such as age and race, as sociodemographic differences can play a role in the sources used and the degree of credibleness assigned (Paige, Krieger, & Stellefson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such issues help to illustrate the importance of eHealth literacy and suggest that we may need to think more carefully about how to support different individuals when making trust judgements about online health information [9]; [46]. This may be particularly important when PEx are present as we know that PEx can help trigger a homophily 'patients like me' response that may mean individuals are yet more vulnerable to targeted messages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhang et al (2017) showed that race was an antecedent of using newer technologies, that is, the Whites compare to non-Whites were more likely to use crowd-sourcing sites to search for factual content. The study of Paige et al (2017) on Black/African Americans and Caucasians showed that eHealth literacy was positive antecedent of trust in online health channels (YouTube, Twitter, Pinterest, Facebook, support groups, blogs/diaries) and sources (health care providers, friends and family members, and government organizations). Although the age and gender could not predict the trust in OHI, the noted researchers showed that interaction effects of eHealth literacy with age and gender moderated trust in OHI.…”
Section: Trust In Online Health Informationmentioning
confidence: 99%